Adapting Jane Austen´s Emma: From Literary Text to Digital Afterlife - Silva, Ana Daniela Alcobia Coelho da (2020)
The present thesis aims at studying adaptation both as a process of reappropriation of the past and as a marker of contemporaneity, departing from Jane Austen's (1775-1817) Emma (1815), given the canonical status held by this novelist in literature and in adaptation studies. Acknowledging the present time as one of redefinition for adaptation studies, this thesis frames its discussion of adaptations of Emma not only in relation to key publications in the field (Hutcheon 2013 [2006]; Sanders 2016 [2006]; Cartmell and Whelehan 2010) but also taking into consideration more recent debates, particularly those broadening the scope and reach of adaptation, both inside and outside the academic environment (Newell 2017; Leitch 2017). Thus, recognising the broad scope of adaptation, which includes a variety of cultural products as well as the possibility of diverse intermedia exchanges, my analysis focuses on adaptations from diverse media, including the traditional cinematic and television products but with a particular emphasis on digital, online, and visual objects of the twenty-first century. Aware of the contemporary significance of digital humanities, this thesis intends to contribute to rethinking the place of literature and its subsidiaries in the digital age as well as to the ongoing debates on the (re)definition of adaptation studies as an independent and interdisciplinary field of knowledge. Furthermore, it seeks to describe and understand the cultural and social significance of these adaptations, pnmary objects of consumer involvement in an intended participatory culture (Jenkins 2006), and to underscore their potential for critical engagement in an age of globalisation and social media.